Identifying agglomeration shadows: long-run evidence from ancient ports - Hornbeck, Richard; Michaels, Guy; Rauch, Ferdinand (AWI discussion paper series, 2024)
We examine "agglomeration shadows" that emerge around large cities, which discourage some economic activities in nearby areas. Identifying agglomeration shadows is complicated, however, by endogenous city formation and "wave interference" that we show in simulations. We use the locations of ancient ports near the Mediterranean, which seeded modern cities, to estimate agglomeration shadows cast on nearby areas. We find that empirically, as in the simulations, detectable agglomeration shadows emerge for large cities around ancient ports. These patterns extend to modern city locations more generally, and illustrate how encouraging growth in particular places can discourage growth of nearby areas.
Keywords: Graue Literatur